Corporate governance mechanisms and accretive share buyback to meet or beat earnings per share forecast - Chandren, Sitraselvi; Ahmad, Zamri; Ali, Ruhani (Universiti Malaysia Sarawak, 2015)
This study examines the Malaysian accretive share buybacks firms from year 2001 to 2008 to determine the relationship between the corporate governance mechanisms and accretive share buybacks, the earnings management device to meet or beat earnings per share (EPS) forecast. The regression results of this study reports the significant effect on the relationship between corporate governance and accretive share buyback. Basically, there is positive effect on the relationship between the board independence, CEO duality and board size with the accretive share buyback to meet or beat EPS forecast (MBEF). Multiple directorships and managerial ownership documents a negative relationship with accretive share buyback to MBEF. However, this study identified insignificant relationship between board meetings and accretive share buyback. Using the accretive share buyback as an earnings management proxy is a new contribution to determine the roles of corporate governance on accretive share buyback to MBEF rather a common study on accruals manipulations and corporate governance mechanisms.